The Role of Islamic Religious Education Teachers in Classroom Management to Shape Students' Noble Character - Nurazizah, Nurazizah; Samsurizal, Samsurizal; Guslianto, Guslianto (LP2M STAI Balaiselasa YPPTI Pesisir Selatan Sumatera Barat, 2025)
Being an Islamic Religious Education teacher is a profession that demands balanced intellectual, emotional, and spiritual abilities. An Islamic Religious Education teacher not only acts as an educator but also serves as a moral guide responsible for shaping the character and morals of students. This study aims to analyze the role of Islamic Religious Education teachers in classroom management through the implementation of effective learning strategies to cultivate students with noble character. This research employs a qualitative method with a case study approach. Data were obtained through observations, interviews, and documentation involving teachers, school officials, and students who were selected using a purposive sampling technique. All data were analyzed using the Miles and Huberman interactive analysis model. The results show that Islamic Religious Education teachers strive to implement effective classroom management by balancing firmness and empathy in enforcing rules, involving students in rule-setting, understanding student behavior through a personal approach, and providing support and motivation in learning. These efforts contribute to creating a conducive learning environment oriented toward the development of students' noble character. However, this study also found challenges, including low discipline and learning motivation among some students. The findings are expected to serve as a reference for developing classroom management strategies based on Islamic values, emphasizing a balance among cognitive, affective, and spiritual aspects in character formation.